Natural Language Processing: Emerging Neural Approaches and Applications - Esposito, Massimo; Masala, Giovanni Luca; Minutolo, Aniello; Pota, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue highlights the most recent research being carried out in the NLP field to discuss relative open issues, with a particular focus on both emerging approaches for language learning, understanding, production, and grounding interactively or autonomously from data in cognitive and neural systems, as well as on their potential or real applications in different domains.